“Análisis financiero a la empresa DICAMED-RC CIA. LTDA., de la ciudad de Loja, periodo 2021-2022”. - Cueva Cueva, Dalton Miguel (2024)
This work is entitled "Financial analysis of the company DICAMED-RC Ltd. of the city of Loja, period 2021-2022". Using a variety of techniques of financial analysis to provide a comprehensive view of the company's economic performance, the main objective of this work is to comprehensively evaluate the company's financial situation. Analysis includes both horizontal and vertical analysis, which facilitate the understanding of the structure of the financial statements in percentage terms as well as observing trends and changes in financial figures over time. A company's performance in critical areas is also measured by key financial indicators, such as liquidity, profitability, solvency, and efficiency. This study employs an adequate methodology, including inductive, deductive, analytical, scientific, and mathematical approaches. These methods allow collecting, analyzing and synthesizing the company's financial information accurately, ensuring the validity and reliability of the results obtained. During the years 2021 and 2022, DICAMED-RC Ltd ́s financial statements were reviewed in order to identify strengths, weaknesses, opportunities, and threats in its financial management. The results of the financial analysis reveal details about the company's capital structure, its asset utilization efficiency, and its profitability potential. The study also identifies critical areas that require immediate attention, such as liquidity management and debt management, which are essential to improving the company's solvency. Based on these findings, strategic recommendations are offered that are designed to optimize the company's financial management, improve its profitability and ensure its long-term sustainability. As part of this project, DICAMED-RC Ltd. will receive a detailed diagnosis of its financial situation as well as a framework in which it can implement more effective financial strategies, adapt to changes in the economic environment, and make informed decisions that contribute to its growth and stability.